Online shopping behavior among academic population in local IPTA - Jamaludin, Roslan; Ahmad, Azizah; Saleh, Abdul Razak (2002)
This paper presents a survey on shopping behavior over the Internet among lecturers and students in local public universities in Malaysia. Questionnaires are divided into 3 parts; profile of respondents, shopping behavior and respondent's opinions regarding their perception on privacy and security over the Internet.Data are analyzed base on frequency and cross tabulation.From the returned questionnaires, 22.2% lecturers and 5.8% students have experienced online shopping with the reasons being convenience and availability of products and services in the Internet.Many of them especially lecturers purchased less than three time monthly and reading materials being the most products bought online.Respondents who do not shop simply because they don't trust (privacy and security) and many students never tried it.Other issues are also asked e.g. security and privacy are vital, 56.9% lecturers and 63.4% students not willing to use credit cards, slightly more than half not ready to exposed their personal detail in the web, and privacy being an important factor in using the internet.